Socialization And Distribution Of The Al-Quran To Mu'alaf In Karo Regency, North Sumatra Province - Meilany, Merry; Erman, Nilam; Winario, Mohd; Harahap, Ahmad Muda; Simbolon, Muhammad Iran (EL-EMIR INSTITUTE, 2024)
The activity of distributing Al-Quran to 9 villages in Karo Regency is part of efforts to increase understanding and appreciation of Islamic teachings in the region. The main aim of this activity is to provide wider access for village communities to obtain and understand the Al-Quran. The methods used in this activity include identifying villages that need distribution of the Al-Quran, contact with local community leaders, establishing Al-Quran study classes, and distributing the Al-Quran directly to village communities. Apart from that, monitoring and evaluation was also carried out on the development of the village community's understanding of the Al-Quran after receiving the Al-Quran. The results of this activity show an increase in village community interest in understanding and practicing the teachings of the Koran. Village communities also appear to be more open to discussing and asking questions about the contents of the Koran, so that interactions between village communities and their understanding of the Koran become better. Thus, it is hoped that the activity of distributing the Al-Quran to 9 villages in Karo Regency will provide great benefits to the village community in deepening their understanding of the Islamic religion, so that it can have a positive impact on their spiritual and social progress.